Modeling and Analysis of Actuators in Multi-Pump Waterjet Propulsion Systems - Shuli Jia; Yinuo Guo; Yuxue Liu; Dali Wei; Chong Qu; Liyong Ma (Journal of Marine Science and Engineering)
Waterjet propulsion, which generates thrust by ejecting water jets, has attracted significant attention in modern high-performance vessels due to its efficiency, superior cavitation resistance, and excellent maneuverability. While previous research has primarily concentrated on optimizing the overall performance of waterjet propulsion systems, insufficient attention has been paid to the detailed dynamic modeling of actuators in multi-pump systems, a critical component for improving system control precision. This paper addresses this gap by developing dynamic models for the reversing bucket and rudder angle actuators in marine waterjet propulsion systems. Based on an in-depth analysis of their working principles and operational parameters, transfer function models are established to simulate actuator performance under various conditions, including wear, hydraulic oil leakage, and external disturbances. Key influencing factors for each condition are identified, and corresponding parameter-setting models are constructed. The models’ response speed and steady-state accuracy are validated through step and ramp tests, confirming their effectiveness and reliability. The proposed model is verified with real measurement experiments and comparisons. The findings of this study contribute new insights into the dynamic behavior of multi-pump waterjet propulsion systems and provide a solid theoretical foundation for the future development of optimized control strategies in complex marine propulsion environments.